The influence of German settlers on the formation and development of an industrial town in Habsburg Bosnia: Teslić (1878 - 1918) - Gavrilović, Darko; Vasin, Goran; Mikavica, Dejan; Đukičin Vučković, Smiljana; Ivanović Bibić, Ljubica; Stojsavljević, Rastislav (Geographica Pannonica, 2018)
This paper studies the formation and development of the Bosnian town of Teslić from the Austro-Hungarian occupation of Bosnia and Herzegovina in 1878 to the end of the First World War in 1918. The goal is to emphasize the significant characteristics of the town’s development: the spread of capitalism; economic modernization; the arrival of a non-Slavic, predominantly German population; and the town as the leader of industrialization in Bosnia and Herzegovina. The industrial origin of Teslić and its structure demonstrate Austria-Hungary’s need to economically integrate Bosnia and Herzegovina into its state area. The aim of this paper is to show to what extent the dynamics of industrial development influenced the town’s formation and to see how the colonist population, which was mostly of German origin, influenced the industrial development and social life of the town.